Legislating Rights: Basic Law Article 23, National Security, and Human Rights in Hong Kong - Kellogg, Tom (Columbia Journal of Asian Law, 2004)
September 5, 2003 may someday be recognized as one of the key dates in Hong Kong history. On that day, Chief Executive Tung Chee-Hwa announced that he was withdrawing the government’s proposals to amend Hong Kong’s national security law. The announcement came roughly one year after the proposals were first introduced, and only two months after the largest public protests in Hong Kong since 1989, when the people of Hong Kong took to the streets in support of the pro-democracy movement in Tiananmen Square in Beijing. On July 1, 2003, an estimated 500,000 people marched through the streets of Hong Kong in order to voice their disapproval for the government’s proposed Article 23 legislation, which was due to be passed within a matter of weeks. It was a rare and thrilling example of the people of Hong Kong making their voices heard, such that the government and pro-Beijing political parties could ill afford to ignore them. Although the Chief Executive admitted that he was shaken by the protests, Tung did not immediately give up on his legislative proposals. Instead he delayed, hoping to find a politically tenable way forward. Not until the two largest pro-Beijing political parties announced that they would withdraw their support for the legislation if it came to a vote in the Legislative Council (“LegCo”) did the Chief Executive finally yield. His September 2003 retreat on Article 23 does not mean that the issue is dead, however. The government might revive its proposals at a later time if it feels that the political winds have changed sufficiently to allow for a second try.